HHV-6 Specific T-Cell Immunity in Healthy Children and Adolescents - Schwarz, Christine M.; Strenger, Volker; Strohmaier, Heimo; Singer, Georg; Kaiser, Margarita; Raicht, Andrea; Schwinger, Wolfgang; Urban, Christian (Frontiers in Pediatrics, 2018)
Objective – Primary infection with human herpes virus 6 (mainly HHV-6B) commonly occurs in the first two years of life leading to persistence and the possibility of virus reactivation later in life. Consequently, a specific cellular immune response is essential for effective control of virus reactivation. We have studied cell-mediated immune response to HHV-6 (U54) in healthy children and adolescents. Materials and Methods - By flow cytometry, the amount of cytokine (interferon gamma – IFN- γ, interleukin 2 – IL-2, tumour necrosis factor alpha – TNF-α) secreting T-cells were measured after 10 days of pre-sensitization and 6 hours of re-stimulation with mixtures of pooled overlapping peptides from U54, staphylococcal enterotoxin B (SEB, positive control) or Actin (negative control) in healthy children and adolescents without any underlying immune disorder or infectious disease. Results - All individuals showed a virus-specific response for at least one cytokine in either CD4+ or CD8+ cells. Percentages of individuals with HHV-6-specific TNF-α response in CD4+ (48% of individuals) as well as CD8+ (56% of individuals) were always the highest. Our data show significantly higher frequencies of HHV-6-specific TNF-α producing CD8+ T-cells in individuals older than 10 years of life (p=0.033). Additionally, the frequency of HHV-6 specific TNF-α producing CD8+ T-cells positively correlated with the age of the individuals. Linear regression analysis showed a positive relation between age and frequency of HHV-6-specific TNF-α producing CD8+ T-cells. Conclusion - Results indicate that T-cell immune response against HHV-6 is commonly detectable in healthy children and adolescents with higher frequencies of antigen-specific T-cells in older children and adolescents possibly reflecting repeated stimulation by viral persistence and subclinical reactivation.